2021
DOI: 10.1186/s42358-021-00209-0
|View full text |Cite
|
Sign up to set email alerts
|

Lung involvement prevalence in patients with early rheumatoid arthritis without known pulmonary disease: a multicentric cross sectional study

Abstract: Background Clinically evident interstitial lung disease (ILD) affects between 10 and 42% of the patients with rheumatoid arthritis (RA). Airway involvement seems to be even more common. Most of the available evidence comes from studies performed in established RA patients. The aim of our study was to know the prevalence of non-diagnosed lung disease (airway and interstitial involvement) in patients with early RA and look for associated factors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
0
12
0
5
Order By: Relevance
“…Paulin et al found that a signi cant percentage (72.2%, 60/83) of early RA patients had abnormal results on HRCT scans. In addition, patients with lung involvement had notably lower FVC% and DLCO% values, as well as higher RV/TLC values (24). Pulmonary function test parameters, such as %DLCO, FEV1/FVC, and %FEF25-75, have been used for assessing functional impairment in pulmonary manifestations linked to RA (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…Paulin et al found that a signi cant percentage (72.2%, 60/83) of early RA patients had abnormal results on HRCT scans. In addition, patients with lung involvement had notably lower FVC% and DLCO% values, as well as higher RV/TLC values (24). Pulmonary function test parameters, such as %DLCO, FEV1/FVC, and %FEF25-75, have been used for assessing functional impairment in pulmonary manifestations linked to RA (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, RA patients were more numerous in the RU cohort than in the PU cohort. This could be explained by the low incidence of significant ILD in early RA [31]. No significant differences in the prevalence of classification criteria between the two cohorts of RA patients were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Second, with the adoption of HRCT in clinical practice, an increase in RA-ILD prevalence has been observed over time ( 16 ). ILD has been detected in up to 7.5% subjects with early RA ( 17 ), while interstitial lung abnormalities (ILA, vide infra ) may be more common ( 18 ). It has been estimated that 10% patients with established RA have clinically significant ILD (i.e., signs and symptoms, latent respiratory insufficiency, severe lung function impairment) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%